Discussion of The Multiperiod Information Content of Accounting Earnings: Confirmation and Contradictions of Previous Earnings Reports - Landsman, Wayne R. (Journal of Accounting Research, 1989)
Wayne R. Landsman, Discussion of The Multiperiod Information Content of Accounting Earnings: Confirmation and Contradictions of Previous Earnings Reports, Journal of Accounting Research, Vol. 27, Current Studies on The Information Content of Accounting Earnings (1989), pp. 80-84